2000
DOI: 10.1177/104063870001200415
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cystic Disease of the Liver and Kidney in a Pygmy Goat

Abstract: A 1-month-old pygmy goat was presented with abdominal distension and hematuria. Anemia, leukocytosis, and increased bilirubin and blood urea nitrogen levels suggested renal and hepatic disease. Radiographs revealed bilateral renomegaly, and ultrasound confirmed bilateral hydronephrosis. Necropsy findings determined that the renomegaly was due in part to edema and marked cystic tubular distension. Similarly, intrahepatic bile ducts were ectatic. The character and distribution of the gross and histologic lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
(19 reference statements)
0
2
1
Order By: Relevance
“…Reported extrarenal manifestations of PKD in animals include biliary and pancreatic cysts. 2,6,7,9,10,15 Pancreatic lesions were not observed in the present case.…”
Section: Sources and Manufacturerscontrasting
confidence: 54%
See 1 more Smart Citation
“…Reported extrarenal manifestations of PKD in animals include biliary and pancreatic cysts. 2,6,7,9,10,15 Pancreatic lesions were not observed in the present case.…”
Section: Sources and Manufacturerscontrasting
confidence: 54%
“…The autosomal recessive form is rare, often diagnosed in early infancy by massive nephromegaly, and is rapidly progressive. 17 Syndromes resembling both the recessive and dominant forms of human PKD have been recognized in animals including cats, 1,2 where Persian cats appear disproportionately affected, 8 dogs, 9,15 mice, 13 pigs, raccoons, 5 and ruminants such as cattle, 14 goats, 7,10 sheep, 3 and springbok (Antidorcas marsupialis). 6 To the authors' knowledge, PKD has not been reported in any member of the family Cervidae.…”
mentioning
confidence: 99%
“…paratuberculosis in both pygmy goats and Cameroon sheep (Weber et al 1992) and congenital cystic disease of the liver and kidney in a pygmy goat (Newman et al 2000). None of these situations or infections has so far been observed in the small ruminants of the attica zoological park.…”
Section: Discussionmentioning
confidence: 99%